REVIEW OF PARASITIC WASP SUBFAMILY EULOPHINAE (HYMENOPTERA: EULOPHIDAE) WITH SPECIAL REFERENCE OF THE TRIBE CIRROSPILINI - Ubaidillah , Rosichon (Treubia, 2015)
The Cirrospilini LaSalle, 2000, belongs to the Eulophinae, along with Eulophini and Elasmini. This tribe consists of about 17 genera and almost 300 species, which are ectoparasitoids, mainly on Diptera, Lepidoptera and Coleoptera in semi-concealed situations. Some species may act as obligate or facultative hyperparasitoids and a few species are gall-formers. Historically, the genera included in the Cirrospilini have been placed in the Eulophinae and the Elachertinae sensu Ashmead, 1904. However, the relationships and the placement of genera into subfamilies or tribes have always been problematical. Based on the current evidence, it appears that the Cirrospilini is a monophyletic taxon and the sister-group of the Eulophini plus Elasmini. This paper summarizes the current taxonomic status and systematic background of the Cirrospilini.